PRINCIPLES OF LABELLING OF AUTOCHTONOUS CHEESES WITH GEOGRAPHICAL ORIGIN - Ostojić, Mihailo; Topisirović, Ljubiša (Economics of Agriculture, 2006)
Bearing in mind the increase of human population, development of new technologies and intensive care of human health, new challenges for scientists appeared. In the fields of fermented food based on various milks modern trends are going to production of so called functional food, which has health promoting activity besides nutritional value. Autochthonous cheeses manufacturing within the Balkan area has very long tradition. These cheeses are produced without using any known starter culture. Therefore, studying all aspects of such cheeses manufacturing is very important. This approach will assure continuation of traditional way of cheeses manufacturing at the original places where they are originally produced. Moreover, research of this kind will open possibility for introduction of autochthonous cheeses production at either semi-industrial or industrial level or their presentation on different markets. The laws on patenting, brand protection or geographical origin declaration are giving the possibilities for protection of autochthonous cheeses. It is not unrealistic to expect that such products will accept on European and other markets. Therefore, the strategy is established to develop the technological process for autochthonous cheese production in the region of mountain Zlatar. The developed technology will be based on the use of starter cultures, which will be constructed of specific lactic acid bacteria (LAB). LAB will be isolated from specific localities on Zlatar, characterized at the molecular genetics level and used for construction of starter cultures.